If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-19=6(x-2)-7
We move all terms to the left:
6x-19-(6(x-2)-7)=0
We calculate terms in parentheses: -(6(x-2)-7), so:We get rid of parentheses
6(x-2)-7
We multiply parentheses
6x-12-7
We add all the numbers together, and all the variables
6x-19
Back to the equation:
-(6x-19)
6x-6x+19-19=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 24m=48 | | 3x+90+x=90 | | 3x+90+x=80 | | 3/4(x)-1.7=-6.82 | | x÷4=28—x÷44=28—4x=7 | | 12,6x=6.2x+88 | | c/10=2/15 | | 7x2+6x-1=0 | | 6f=150 | | 3(5x-2)=10x+9 | | 9x+14=-139 | | 100/x=22/55 | | n/6=7/3 | | j−7=2j | | 5(6x+7)=-6x-1 | | 5^4{x-9}=3^6{x} | | W/5-w/10=10 | | 7z+1=10+6z | | 3p+3(1-p)=-1(p+2) | | -15-14x=-141 | | y2+12y=−4y | | 8j+2=8+2j | | x/8=1.6 | | 35=7i | | a÷3=9 | | g(6)=36 | | -8x^2+8x+7=9 | | 5b^2-2b-4=-5 | | 3b7=2 | | 84=6x+5x+7 | | a-¼=2½ | | 35=100+x |